2018
DOI: 10.18805/ag.r-1711
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable Grafting: A Surgical Approach to combat biotic and abiotic stresses- A review

Abstract: Vegetables are nutritionally rich, high-valued crops and remunerative enough to replace subsistence farming. However, vegetables are highly sensitive to climatic vagaries and sudden irregularities in weather factors at any phase of crop growth can affect the normal growth, flowering, fruit development and subsequently the yield. Grafting in vegetable has emerged as a promising surgical alternative over relatively slow conventional breeding methods aimed at increasing tolerance to biotic and abiotic stresses. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 67 publications
0
19
0
Order By: Relevance
“…Tests were carried out with cleft-grafted and non-grafted plants rub-inoculated on the first leaf above the graft junction with sap extracted from infected plants and grown under glasshouse [ 62 , 63 , 64 ] or exposed to field inoculum (this review). According to Kumar et al [ 38 ], complete repair of graft wound would be achieved between 7 and 10 days after grafting, thus we were confident that by the time of inoculation, continuous cambial connections between scion and rootstock had been restored. In glasshouse tests, plants were grown and maintained at 24 ± 2 °C with 16 h photoperiod and monitored daily for disease symptoms.…”
Section: Screening Of Solanum Spp Germplasmmentioning
confidence: 67%
See 2 more Smart Citations
“…Tests were carried out with cleft-grafted and non-grafted plants rub-inoculated on the first leaf above the graft junction with sap extracted from infected plants and grown under glasshouse [ 62 , 63 , 64 ] or exposed to field inoculum (this review). According to Kumar et al [ 38 ], complete repair of graft wound would be achieved between 7 and 10 days after grafting, thus we were confident that by the time of inoculation, continuous cambial connections between scion and rootstock had been restored. In glasshouse tests, plants were grown and maintained at 24 ± 2 °C with 16 h photoperiod and monitored daily for disease symptoms.…”
Section: Screening Of Solanum Spp Germplasmmentioning
confidence: 67%
“…Nonetheless, suitable levels of resistance against root-knot nematodes and Phytophthora capsici were attained in sweet pepper grafted on Capsicum annuum accessions “AR96023” and “AF2638,” respectively. Finally, this list could not be exhaustive without including the control of Verticillium wilts obtained by grafting seed-propagated globe artichoke hybrids onto cardoon [ 37 ] as well as the list of potential rootstocks with special characteristics to manage biotic and abiotic stresses in tomato, eggplant, chili, potato, cucumber, muskmelon, pumpkin, and wax gourd reported by Kumar et al [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Savvas et al [16] also reported that grafting resulted in increased fruit and thus yield, when plants were exposed to low or moderate salinity in hydroponic system. This variability among reported findings demonstrates the importance of optimizing rootstock/scion combinations for each growth environment, including growing system, type of soil, day and night temperatures, and fertigation [21]. Each grafting combination should be tested under the anticipated salinity-exposure conditions before deciding on its suitability as a means to enhance the salt resistance of commercial greenhouse crops [16].…”
Section: Discussionmentioning
confidence: 99%
“…RKN resistant germplasm comprises both cultivars and rootstocks. Grafting is a useful option when no commercial RKN resistant cultivars are available or when other resistance/tolerance genes are needed for complementing the management of other economically important soilborne diseases and/or abiotic stresses but have not been introgressed into commercial cultivars (Kumar et al ., ). Despite these advantages, plant resistance must be used properly to avoid selection for virulence by the repeated cultivation of plant germplasm carrying the same resistance ( R ) gene (Verdejo‐Lucas et al ., ; Giné & Sorribas, ); and also to reduce the expression of plant resistance due to high soil temperatures (Araujo et al ., ).…”
Section: Introductionmentioning
confidence: 97%